Tinjauan Tentang Perjanjian Perkawinan Dalam Pandangan Hukum Nasional - Christina Bagenda (Jayapangus Press, 2021)
A marriage agreement is an agreement that regulates the result of a marriage bond. In Indonesia, marriage agreements are allowed to be made since the enactment of the Civil Code. This marriage agreement is then reaffirmed in the Marriage Law No. 1 of 1974. Marriage agreements are part of the field of family law as regulated in Book I of the Civil Code (BW). Marriage agreement arrangements are described in Chapter VII articles 139 s / d 154. Broadly speaking, a marriage agreement is valid and binds the parties / bride and groom in a marriage. In the Marriage Law no. 1 of 1974, the Marriage Agreement is found in Chapter V, which contains one article, namely article 29. One of the principles contained in this law regarding marriage agreements is the equal rights and position of husband and wife. Marriage agreements, which are still taboo in the general public, have now become a trend among artists, officials, businessmen, or people with a lot of money. They generally have the view that with the existence of a marriage agreement, the assets of each partner are still safe and belong to them. In fact, they are not willing if their property mixes with their spouse because usually a divorced husband and wife will fuss over the distribution of assets gono gini. They were fighting over which part of their respective assets. If there is a marriage agreement, the distribution of the gono gini assets will be easier because it can be separated which is the property of the gono gini and which is not. Thus the marriage agreement functions as a control for problems at a later date